Controlling the Black Friday Frenzy in 2020 - Robson, Karen (London : SAGE Publications: SAGE Business Cases Originals, 2020)
This case discusses the massive shopping events that occur annually in the days after U.S. Thanksgiving and the recent decision made by Walmart and Target (two of the biggest players in the sales event) to close their doors on Thanksgiving Day this year. Students are asked to assess consumer behavior around this annual sales event, to discuss why the stores have changed their approach in 2020, and to speculate what this may signal for the future of Black Friday.
Includes bibliographical references.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Health